HOAKS Sebagai Konstruksi Sosial Untuk Kepentingan Politik Praktis Dalam Pilgub DKI Jakarta - Moh. Abu Na’im (IAI Darussalam, 2017)
This article describes the phenomenon of hoaks that occurred in the political momentum in Jakarta. Hoaks do not stand alone. There is a greater importance behind it. Based on data released by Kompas, during the political momentum, the distribution of hoaks is increasing. What should be discussed is the interests of hoaks and their relation to practical politics, as well as the encouraging factors for the phenomenon of hoaks. The phenomenon of hoaks will be exposed to social construction as Peter L. Berger and Thomas Luckman create a theoretical framework for mass media communication. As a social construction, hoaks are related to three continuous process frameworks. Covers externalization, objectivization, and internalization. In addition, hoaks can also be approached with Framing theory. Where in the media coverage there has been a subjective interest that lies behind it. With some of these approaches, hoaks is a political phenomenon that enters the media network to construct the community according to the interests behind it. One way to construct it by doing framing and also spreading hate speech that attacked using SARA pretext against political opponents in Pilgub in DKI Jakarta